The Responsibility of Telecommunication Service Providers Against Recycled Telephone Numbers from the Consumer Protection Law - Winfritz Jeremia Abner; Christian Andersen (PT Mattawang Mediatama Solution, 2023)
The purpose of this article is to find out the responsibilities of telecommunications service providers, in the current digital era, phone numbers are one of the most necessary factors in the digital sphere, such as registration, entry access, population data, and so on. Phone numbers become the daily identity of user's business life. where there are so many online platforms such as social media networks, applications, emails, and important sites that are connected directly through a phone number. troubles will occur when the phone number used has been inactive for a long time which will result in the phone number being recycled (recycle number) and will be used by new users. From this, it will have the potential to endanger old users because the identity data on the old user's phone number is still attached to applications, social media networks, or other services such as pay later, e-banking, get contacts, and so on. New users will also be able to feel the same way if the old users have done harmful actions on the number such as illegal online loans that will disturb new users due to the terror given. The method that will be used in this article is normative juridical, namely the concept of analyzing liability through statutory legal materials in terms of Law Number 8 of 1999 concerning Consumer Protection. Therefore, the user as the consumer of the telecommunications service provider can make efforts in the form of a request for accountability to the communication service provider based on the losses incurred for the user. It is also necessary to have standard operating regulations for telecommunications service providers on recycled phone numbers (recycle numbers) to create a database that can be disclosed to the public regarding phone numbers that have the status of recycled phone numbers (recycle numbers) to prevent misuse of data in phone numbers.